Late diagnosis of Takayasu's arteritis with repeated attacks of heart failure and uncontrolled hypertension due to abdominal aortic thrombosis: Case report and review of the literature. (2nd November 2015) - Wang, Huan; Lai, Baochun; Wu, Xiaoying; Han, Tao; Chen, Hui
Abstract : Takayasu's arteritis (TA) is a chronic, idiopathic, inflammatory disease affecting the aorta and its branches. To date, only one case involving abdominal aortic thrombosis due to TA has been reported. After bilateral artificial subclavian–iliac bypass, a case of abdominal aortic thrombosis due to TA received a delayed diagnosis in a 44-year-old Chinese male who experienced recurrent episodes of heart failure and uncontrolled hypertension with claudication of two extremities. Abdominal color Doppler sonography and computed tomography aortography (CTA) showed occlusion of the abdominal aorta and bilateral renal artery stenosis. After vascular bypass and during 1 year follow-up, his cardiac function improved and blood pressure was well controlled, with reduced serum creatinine. Postoperative CTA still showed abdominal aortic thrombosis resulting in arterial occlusion extending from the left renal artery initial segment level to the bilateral common iliac artery and the bifurcation of the renal artery, except for the vascular bypass. Abdominal aortic thrombosis due to TA is very rare and potentially life threatening, probably becoming an atherosclerosis risk factor. Doppler sonography and CTA results are important for diagnosis. Artificial vascular bypass can be used for TA in debilitated patients with diffuse aortic disease.